PENGARUH DOMINASI OTAK KIRI DAN OTAK KANAN TERHADAP PRESTASI BELAJAR ARITMETIKA DAN GEOMETRI PADA SISWA KELAS V - Anggun Henny Kurniawati (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2016)
This research is quantitative. Implemented in the first semester of the academic year 2012/2013 in Madiun Lor SDN class V. The sample in this research is class VA and VB class. The data collection technique using the test methods and non-test. The sampling technique in this study using full retrieval. The instrument used is the learning achievement test arithmetic and geometry, while the non-test methods such as brain dominance questionnaire. Learning achievement test arithmetic and geometry are used to determine the ability of students to work on the problems of arithmetic and geometry while brain dominance questionnaire used to obtain data student brain dominance. These three research instruments before tested first validated.Hypothesis testing using the Mann Whitney test with significance level0.05. To test the hypothesis of learning achievement aritmetrika Zhitung (= 0.1962) Zhitung (= 1.645), then H0 is accepted. conclusion that learning achievement in the field of arithmetic left brain dominant student is not better than learning achievement in the field of arithmetic right brain dominant students. To test the hypothesis of learning achievements obtained Zhitung geometry (= 0.912)Ztabel (= 1.645) so that H0 is accepted. conclusion that learning achievement inGeometry field right brain dominant student is not better thanThe learning achievement in the field of geometry students left brain dominant.Keywords: brain dominance, school performance and achievement of learning arithmetic geometry.